QSOX1 inhibits autophagic flux in breast cancer cells. - Laura Poillet (PLoS ONE, 2014)
The QSOX1 protein (Quiescin Sulfhydryl oxidase 1) catalyzes the formation of disulfide bonds and is involved in the folding and stability of proteins. More recently, QSOX1 has been associated with tumorigenesis and protection against cellular stress. It has been demonstrated in our laboratory that QSOX1 reduces proliferation, migration and invasion of breast cancer cells in vitro and reduces tumor growth in vivo. In addition, QSOX1 expression has been shown to be induced by oxidative or ER stress and to prevent cell death linked to these stressors. Given the function of QSOX1 in these two processes, which have been previously linked to autophagy, we wondered whether QSOX1 might be regulated by autophagy inducers and play a role in this catabolic process. To answer this question, we used in vitro models of breast cancer cells in which QSOX1 was overexpressed (MCF-7) or extinguished (MDA-MB-231). We first showed that QSOX1 expression is induced following amino acid starvation and maintains cellular homeostasis. Our results also indicated that QSOX1 inhibits autophagy through the inhibition of autophagosome/lysosome fusion. Moreover, we demonstrated that inhibitors of autophagy mimic the effect of QSOX1 on cell invasion, suggesting that its role in this process is linked to the autophagy pathway. Previously published data demonstrated that extinction of QSOX1 promotes tumor growth in NOG mice. In this study, we further demonstrated that QSOX1 null tumors present lower levels of the p62 protein. Altogether, our results demonstrate for the first time a role of QSOX1 in autophagy in breast cancer cells and tumors.